Classics in Environmental Criminology. - Andresen, Martin A. (CRC Press, 2010)
A comprehensive collection of seminal pieces on environmental criminology. It focuses on the role that the immediate environment plays in the occurrence of a crime. It demonstrates that a careful analysis of environmental factors is key to understanding the causes of crime, solving crimes, and helping to predict and prevent them.